2022
DOI: 10.33755/jkk.v8i4.442
|View full text |Cite
|
Sign up to set email alerts
|

Factor Affecting Treatment Compliance in TB Patients

Abstract: Aims: Pulmonary Tuberculosis is a disease caused by  Mycobacterium tuberculosis that invades the lungs. Indonesia ranks second as the country with the highest number of pulmonary TB in the world.  The treatment coverage of Pulmonary TB in Indonesia in 2022 is only 25% of the target (80%). One of the risk factors that cause treatment failure is medication adherence. Objective:  This study aims to determine the factors that influence medication adherence in patients with pulmonary TB.  Methods:  This study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Lucya & Arief's (2022) research also found that family living was significantly associated with medication adherence (p-value 0.018) (38). Family support in the form of financial assistance, affection, attention, enthusiasm, and motivation helps patients to comply with treatment (37).…”
Section: Reinforcing Factor Family Supportmentioning
confidence: 98%
See 4 more Smart Citations
“…Lucya & Arief's (2022) research also found that family living was significantly associated with medication adherence (p-value 0.018) (38). Family support in the form of financial assistance, affection, attention, enthusiasm, and motivation helps patients to comply with treatment (37).…”
Section: Reinforcing Factor Family Supportmentioning
confidence: 98%
“…Older people tend to follow doctors' instructions because they are more responsible, orderly, conscientious, moral, and filial compared to younger people. Older patients tend to be more adherent to treatment because their activity is less dense compared to younger patients so they can seek treatment regularly (38).…”
Section: Predisposing Factors Agementioning
confidence: 99%
See 3 more Smart Citations